(untitled) (International Journal of Innovative Technologies in Economy, 2023)
The role of modern digital technologies in the strategic management of modern construction companies, including the processes of regulating their relations with customers, design, implementation of other functions can hardly be underestimated. This article shows that today a lot of such technologies and information-technical solutions are used: websites are developed, opportunities of Internet sites and platforms are actively used, groups in social networks are created, various software products are used. It is concluded that only the integrated use of these information and digital solutions will give the most effective results. Construction firms increasingly rely on cloud-based project management software like Procore, PlanGrid, and Autodesk BIM 360. These platforms enable real-time collaboration, document sharing, and project tracking. Automation and robotics are being employed in various construction tasks, such as bricklaying, excavation, and concrete pouring. These technologies can increase precision and speed while reducing labor costs. VR and AR are utilized for virtual project walkthroughs, design reviews, and safety training. They enhance communication and understanding among project stakeholders. Blockchain technology is being explored to enhance transparency and security in construction contracts and supply chain management. It can help prevent disputes and streamline payment processes. Digital technologies are increasingly used to optimize construction processes for sustainability. This includes energy-efficient building design, waste reduction, and the use of sustainable materials. To stay competitive in the construction industry, it’s essential to keep up with the latest developments in digital technologies and consider how they can be integrated into your business processes. Additionally, staying informed about industry-specific trends and regulations is crucial for long-term success.